Beautiful origami paper wreaths : handmade Japanese decorations for every occasion - Nagata, Noriko (Tuttle Publishing, 2020)
These origami decorations may look complex and expensive, but they are actually easy to create and will never wilt or shed, making them highly economical! Each wreath is assembled from a number of paper sheets that are folded and then cleverly slotted together. No glue or tape required! The ring itself is held together by the tension of the individual paper pieces using the techniques of modular origami. Full-color, step-by-step instructions help you fold and assemble these beautiful pieces. Different designs are provided for each month of the year-34 in all-and you can endlessly vary the colors and materials, which are readily available in any craft store.